Gender platform communication and knowledge management: looking back 2017 - looking forward to 2018 - Braaten, Yngve; Le Borgne, Ewen (CGIAR Collaborative Platform on Gender Research, 2017)
Presented by Yngve Braaten and Ewen Le Borgne (KIT), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.